Mixed infection by sugarcane mosaic virus and maize rayado fino virus causing breaking yields in maize in são paulo state. - Gonçalves, Marcos César (2007)
The two main viruses infecting maize in Brazil are Sugarcane mosaic virus (SCMV) and Maize rayado fino virus (MRFV), whose main vectors are the aphid Rhopalosiphum maidis and the leafhopper Dalbulus maidis, respectively. MRFV is frequently found in mixed infections with phytoplasms and spiroplasms causing the so-called corn stunting diseases. In a maize commercial field close to Santo Antonio da Posse, São Paulo state, surrounded by sugarcane fields, it was found a high incidence of plants showing mosaic, striping, stunting and cobs with decreased number of grains. Serological analysis with specific antisera detected the presence of SCMV and MRFV in these plants. SCMV infection was also confirmed by RT-PCR with specific primers and sequence analysis. In TEM observations of negatively stained preparations, flexuous (ca.770 nm) and isometric particles (ca.30 nm) were detected. In ultrathin sections, cytoplasmic inclusions, typical of Potyviridae, were observed; neither presence of spiroplasms nor phytoplasms could be noted. These results show that mixed infection by SCMV and MRFV might be responsible for the crop losses.